Perception of medical students regarding the inappropriate use of social media - Padilla Deza, Magaly Milagros (2024)
Introduction. Some scientific publications describe the existence of inappropriate use of social media (SM) by doctors and medical students. One way to prevent them is through the development of educational plans that promote appropriate use of SM since undergraduate level. It is important to incorporate the perceptions of future Peruvian doctors regarding this topic into these plans. Objective. To evaluate the perception of students at a Peruvian medical school regarding the inappropriate use of SM in medicine. Methods. Cross-sectional study, an online questionnaire was applied, the sample was 271 students. The perception regarding four types of inappropriate use of SM was evaluated through 16 fictitious cases, as well as its correlation with the year of studies. Results. More than 50% of students considered 13 of the 16 cases of inappropriate use of social media to be inappropriate or highly inappropriate, discrimination by physicians was considered the most inappropriate. The perception of inappropriate use regarding publications with a negative influence on the professional image was high (78.36%). A low correlation was observed between the year of study and the perception of breaches of confidentiality or privacy, as well as disparaging comments about physicians. Cases involving physicians were perceived as more inappropriate than those involving students. Conclusions. Medical students recognize various forms of inappropriate SM use; however, some situations are not identified as such by the majority. These findings suggest that medical ethics education should include topics related to SM that address the identified gaps.